Statistical Analysis of the Weight and Center-of-Gravity Position of an Empty Container Ship - Tadeusz Szelangiewicz; Katarzyna Żelazny (Applied Sciences)
For the correct execution of the preliminary design of a transport ship, among other things, approximate formulas enabling the calculation of the weight of the unladen ship and the location of the center of gravity are necessary. The aim of the conducted research was to develop approximate formulas for calculating the weight and center of gravity of an empty container ship with a size ranging from 270 TEU to 3100 TEU, depending on the basic design parameters: ship speed V, deadweight DWT, and number of TEU containers. Since the weight of an unladen container ship has a very large impact on the ship’s operating parameters, an additional aim was to obtain regression formulas with greater accuracy than similar formulas published in the literature. Simple and multiple regression methods were used to develop regression formulas. The obtained results were verified on the basis of experimentally measured parameters obtained from built ships. The regression formulas presented in this article are characterized by high accuracy, greater than that of similar formulas published in the literature, and were developed for container ships currently under construction. A novelty of this study is the development of regression formulas for weight classes, which make up the total weight of an unladen ship.